Reviving Radical Traditions of Democracy in Organising for the Future - Tony Brown (Adult Education Research Conference, 2004)
Australian unions have adopted new organising methods to rebuild and develop combative organisations. The vitality involved is tempered by a hostile legal climate that supports flexibility, fragmentation and low wage work. This paper explores the common heritage between the new organising and theories of popular education, radical history and social movement experience that can give strength to these efforts.